2021
DOI: 10.4274/ejbh.galenos.2021.6379
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 On Breast Cancer Management: A Radiological Prespective from A Tertiary Centre

Abstract: Objective: The coronavirus-2019 (COVID-19) pandemic caused delaying breast cancer management, increasing time interval in chemotherapy cycles and surgery. This has implications on radiological manifestation of cancer. Further, we evaluated changes observed in mammography. Materials and Methods:This case control study was conducted from March 25 th , 2020 to August 15 th , 2020 at the Integrated Breast Care Centre, All India Institute of Medical Science Rishikesh (AIIMS), Rishikesh. Sonomammography was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Specifically, one study found an increase in neoadjuvant endocrine therapy [ 49 ], and another study found that women treated during COVID-19 were more likely to receive neoadjuvant endocrine therapy [ 50 ]. While one study found no difference in the time interval from diagnosis to treatment [ 51 ], another study found the time from treatment to surgery increased [ 74 ]. Clinicians do not believe that treatment changes should be continued moving forwards from COVID-19 [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, one study found an increase in neoadjuvant endocrine therapy [ 49 ], and another study found that women treated during COVID-19 were more likely to receive neoadjuvant endocrine therapy [ 50 ]. While one study found no difference in the time interval from diagnosis to treatment [ 51 ], another study found the time from treatment to surgery increased [ 74 ]. Clinicians do not believe that treatment changes should be continued moving forwards from COVID-19 [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, one of the first cases of COVID‐19 was detected in March 2020 in Tokyo, and from April to May 2020, the Japanese government declared a state of emergency in Tokyo and some other prefectures as the daily number of COVID‐19 cases increased exponentially. Consequently, the majority of the hospitals restricted out‐patient visits as an infection control measure against COVID‐19 1 . In addition, some patients refrained from visiting hospitals to avoid contracting the virus 2 .…”
Section: Introductionmentioning
confidence: 99%
“…the majority of the hospitals restricted out-patient visits as an infection control measure against COVID-19. 1 In addition, some patients refrained from visiting hospitals to avoid contracting the virus. 2 Indeed, COVID-19 pandemic has been noted as a cause for interruption of such as radiation therapy during treatment for breast cancer.…”
mentioning
confidence: 99%
“…Consequently, the majority of the hospitals restricted out-patient visits as an infection control measure against COVID-19. 1 In addition, some patients refrained from visiting hospitals to avoid contracting the virus. 2 However, there is not enough information regarding breast cancer patients who are disproportionately affected by the COVID-19 pandemic in terms of continuation of care.…”
Section: Introductionmentioning
confidence: 99%